2009
DOI: 10.1002/uog.7484
|View full text |Cite
|
Sign up to set email alerts
|

Retronasal triangle: a sonographic landmark for the screening of cleft palate in the first trimester

Abstract: Objectives To describe a new first-trimester sonographic landmark, the retronasal triangle, which may be useful in the early screening for cleft palate. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 20 publications
(13 reference statements)
3
122
0
3
Order By: Relevance
“…The retronasal triangle view was recently described as a firsttrimester technique for the sonographic screening of cleft palate. 11 By displaying the primary palate and the frontal processes of the maxilla in the same plane, a characteristic echogenic triangle-shaped structure behind the fetal nose is clearly shown. We noticed that the nasal bones were easily identified in this plane, allowing the opportunity of identifying the nasal bone during the first-trimester scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retronasal triangle view was recently described as a firsttrimester technique for the sonographic screening of cleft palate. 11 By displaying the primary palate and the frontal processes of the maxilla in the same plane, a characteristic echogenic triangle-shaped structure behind the fetal nose is clearly shown. We noticed that the nasal bones were easily identified in this plane, allowing the opportunity of identifying the nasal bone during the first-trimester scan.…”
Section: Discussionmentioning
confidence: 99%
“…10 We have recently described a new technique to evaluate the midface using the coronal plane at the level where the primary palate and frontal processes of the maxilla are simultaneously visualized, which we have named the retronasal triangle view. 11 This technique aims to screen for orofacial clefting in the first trimester. During the routine evaluation of this area in healthy fetuses, it became evident that the nasal bones can also be visualized at the upper tip of the triangle, suggesting that this technique could also be useful for visualizing both nasal bones in a single view (Figure 1).…”
mentioning
confidence: 99%
“…25 Various authors have reported, complete fetal anatomy survey was achieved between 82%-98% depending on the protocol and gestational age at the time of scan. 26 The strength of the study includes the completeness of data, usage of good ultrasound machine for better visualization, the checklist for visualization of structures was based on ISUOG protocol for uniformity and standardization, and all the scans for the study were done by a single experienced radiologist with the same machine.…”
Section: 20mentioning
confidence: 99%
“…Facial landmarks such as tragus, nasion, gnathion, glabella, subnasion, and others were employed to extract sixteen craniofacial measurements for the evaluation of after-birth abnormal/regular orofacial development. Although none of the foetuses evaluated in their study was affected by cleft lip, Sepulveda et al (2010) proposed a novel sonographic landmark typical of the first trimester, the 'retronasal triangle', to be adopted for the early screening of CP. This landmark has been termed this way because coronal plane displays three easily identifiable echogenic lines: the two maxilla frontal processes and the primary palate.…”
Section: Introductionmentioning
confidence: 99%